F1 protein fraction obtained from latex incorporated into CaP-materials improve critical-size defect bone repair in a concentration-dependent manner - Paini, Suelen (2018)
One strategy for bone regenerative engineering is to use matrices associated to osteogenic and angiogenic molecules to increase bone formation. The aim of the present study was to evaluate the efficacy of treatment of extensive cranial bone defects with the F1 protein obtained from latex adsorbed at different concentrations (0,01%, 0,025%, 0,05% e 1%) to two different bonesubstitutes biomaterials, deproteinized bovine bone (DBB) and biphasic calcium phosphate ceramics (pBCP) using a preclinical model in rats. Defects of 8-mm diameter were created in parietal bones of 72 rats filled with the pure biomaterial or carried with the different concentrations of F1 protein, in the microtomographic images a visual analysis of the microtomographic reconstructions of the skull through transverse, coronal and sagittal sections. Subsequently, the segmentation of the defect in the reconstructions will be done through an image processing algorithm to quantify the parameters. Analyzing, in the BP-G group, the total volume of bone (TV), in the CSBD-CG group, the total volume of new bone (TV-NB), and in the treated groups, the total volume of the grafted region (TV/GR), the total volume of new bone (TV-NB) and biomaterials (TV/DBB and TV/pBCP). In tissue sections stained with Hematoxylin and Eosin a descriptive histological analysis was performed to verify the tissue response to treatment with F1 protein and its association with osteoconductive biomaterial and correlate it with the histomorphometric determination to obtain percent values and volume of neoformed bone tissue, biomaterial, bone marrow and soft tissue. In the characterization of DBB and pBCP biomaterials, it was performed through the combined analytical methodology by SEM and SDD-EDS, to analyze external morphology and elemental chemical composition. All the results were compared between the groups by the ANOVA variance analysis and the Tukey tests at the 5% level of significance (Statistica v.5.1, StatSoft). After 12 weeks, defects treated with biomaterials without F1 presented greater bone formation in relation to the control group. The association of 0.025% and 0.05% of F1 plus DBB showed higher bone formation (32.6% and 25.1%, respectively) when compared to pBCP, being 19.3% and 15.1%, respectively. We conclude that the stimulation of angiogenesis and osteogenesis depends on its concentration of F1e and the physicochemical properties of the carrier material.